Design for scalability: A case study of the River City curriculum - Clarke, Jody; Dede, Chris (Journal of Science Education and Technology, 2009)
Publisher: Springer KerkoCite.ItemAlsoKnownAs: 10.1007/s10956-009-9156-4 2339240:QUPKNCUZ 2405685:KM59HIC2

JIME - The Open Learning Initiative: Measuring the Effectiveness of the OLI Statistics Course in Accelerating Student Learning - Lovett, Marsha; Meyer, Oded; Thille, Candace (Journal of Interactive Media in Education, 2008)
The Open Learning Initiative (OLI) is an open educational resources project at Carnegie Mellon University that began in 2002 with a grant from The William and Flora Hewlett Foundation. OLI creates web-based courses that are designed so that students can learn effectively without an instructor. In addition, the courses are often used by instructors to support and complement face-to-face classroom instruction. Our evaluation efforts have investigated OLI courses’ effectiveness in both of these instructional modes – stand-alone and hybrid. This report documents several learning effectiveness studies that were focused on the OLI-Statistics course and conducted during Fall 2005, Spring 2006, and Spring 2007. During the Fall 2005 and Spring 2006 studies, we collected empirical data about the instructional effectiveness of the OLI-Statistics course in stand-alone mode, as compared to traditional instruction. In both of these studies, in-class exam scores showed no significant difference between students in the stand-alone OLI-Statistics course and students in the traditional instructor-led course. In contrast, during the Spring 2007 study, we explored an accelerated learning hypothesis, namely, that learners using the OLI course in hybrid mode will learn the same amount of material in a significantly shorter period of time with equal learning gains, as compared to students in traditional instruction. In this study, results showed that OLI-Statistics students learned a full semester’s worth of material in half as much time and performed as well or better than students learning from traditional instruction over a full semester. Editor: Stephen Godwin (Open University, UK). Reviewers: Tim de Jong (Open University, NL), Elia Tomadaki (Open University, UK), and Stephen Godwin (Open University, UK). Interactive elements: A demonstration of the StatTutor statistics tutorial is available for playback from http://jime.open.ac.uk/2008/14/stattutor_tour/ . The demonstration is in Flash format. http://jime.open.ac.uk/2008/14/stattutor_tour/
Number: 1 Publisher: Ubiquity Press shortDOI: 10/ghcsxd KerkoCite.ItemAlsoKnownAs: 10/ghcsxd 2405685:U4FGVWP3
Keywords: IDR; Mathematics Learning; case studies; design patterns; games; methodology; open learning; pattern languages

Stakeholder Analysis and Social Network Analysis in Natural Resource Management - Prell, Christina; Hubacek, Klaus; Reed, Mark (Society & Natural Resources, 2009)
The increasing use of stakeholder analysis in natural resource management reflects a growing recognition that stakeholders can and should influence environmental decision making. Stakeholder analysis can be used to avoid inflaming conflicts, ensure that the marginalization of certain groups is not reinforced, and fairly represent diverse interests. We present a case study from the Peak District National Park in the United Kingdom, where we used social network analysis to inform stakeholder analysis. This information helped us identify which individuals and categories of stakeholder played more central roles in the network and which were more peripheral. This information guided our next steps for stakeholder selection. The article ends with a discussion on the strengths and limitations of combining social network analysis with stakeholder analysis.
Publisher: Routledge _eprint: https://doi.org/10.1080/08941920802199202 zotzenLib.CopiedFrom: 2339240:TLSREEVC KerkoCite.ItemAlsoKnownAs: 10.1080/08941920802199202 2339240:TLSREEVC 2405685:W8IEPX5K
Keywords: participatory resource management; social network analysis; stakeholder analysis

A Study on The Implementation of English Interactive Radio Instruction (IRI) in Selected Government Primary Schools in Addis Ababa - Alaro, Meseret (Addis Ababa University, 2007)
As its central objective, this study attempts to assess the implementation of English Interactive Radio Instruction (IRI) in selected government primary schools in Addis Ababa. In line with that, the researcher has framed specific questions that address issues related to classroom management, training given to the teachers, links among different stakeholders and the suitability and clarity of the program. Students and teachers of Grade Three from Biherawi Betemengist, Edget Besira , Karalo , Lafto and Salayish Primary Schools are participants of this study .To undertake the study descriptive research design is used . Accordingly, data that is pertinent to the study is collected using different tools such as questionnaire, observation, focus group discussion, interview and document analysis. The findings of the study reveal that the implementation of the program seems to face grave challenges. These mainly emanate from loose link among stakeholders, failure of supplying basic facilities needed to promote the fruitfulness of the program and failure to arrange suitable conditions for the broadcast. Moreover, based on the opinion of the participants, results of the study highlight that in some cases contents of the program is not suitable compared to the students language proficiency .It is also noticed from the findings of the study that classroom practice is not effectively carried out as per the very goal of the program. Despite that, both students and teachers forward positive comments about the utilization of the program for the teaching of English. Based on the findings recommendations for better service and suggestions for further studies are given.
Accepted: 2018-06-20T09:54:22Z KerkoCite.ItemAlsoKnownAs: 2405685:P9GW7UMM

Monitoring basic skills acquisition through rapid learning assessments: A case study from Peru - Abadzi, Helen; Crouch, Luis; Echegaray, Marcela; Pasco, Consuelo; Sampe, Jessyca (PROSPECTS, 2005)
KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-005-1817-3 2339240:QDJBCG9B 2405685:KCL8RYGR

Field-Based Models of Primary Teacher Training: Case Studies of Student Support Systems from Sub-Saharan Africa - Mattson, Elizabeth (Department for International Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:48KESELW
Keywords: C:sub-Saharan Africa; ⛔ No DOI found

An Investigation of Provision of Quality Basic Education in Ghana: A Case Study of Selected Schools in the Central Region - Ampiah, Joseph (Journal of International Cooperation in Education, 2008)
KerkoCite.ItemAlsoKnownAs: 2405685:NDYK3WSP
Keywords: ⛔ No DOI found

An evaluation of the effectiveness of computer assisted learning strategy and expository method of teaching biology: a case study of lumen Christi international high school, Uromi, Nigeria - Imhanlahimi, E. O.; Imhanlahimi, R. E. (Journal of Social Sciences, 2008)
Publisher: Taylor & Francis KerkoCite.ItemAlsoKnownAs: 10.1080/09718923.2008.11892621 10/ggppsj 2339240:BM5PL29D 2405685:JYCRNIYS

National Policies that Connect ICT-Based Education Reform to Economic and Social Development - Kozma, Robert B. (Human Technology: An Interdisciplinary Journal on Humans in ICT Environments, 2005)
Information and communication technology (ICT) is a principal driver of economic development and social change, worldwide. In many countries, the need for economic and social development is used to justify investments in educational reform and in educational ICT. Yet the connections between national development goals and ICT-based education reform are often more rhetorical than programmatic. This paper identifies the factors that influence economic growth and shows how they supported economic and social development in three national case studies: Singapore, Finland, and Egypt. It describes a systemic framework of growth factors and types of development that can be used to analyze national policies and connect ICT-based education reform to national economic and social development goals. And it discusses how the coordination of policies within and across ministries can support a nation’s efforts to improve economic and social conditions. The paper highlights special concerns and challenges of developing countries.
shortDOI: 10/gf54xx KerkoCite.ItemAlsoKnownAs: 10.17011/ht/urn.2005355 10/gf54xx 2339240:U6EMQ8ZJ 2339240:XP4CBBBW 2405685:4IF64UER 2405685:MUCISL2Q

Computer aided instruction for out-of-school children in India: An impact study in Andhra Pradesh - Karnati, Romilla (University of Pennsylvania, 2008)
India has the largest number of out-of-school children, the majority of whom are girls. Against this backdrop, the Bridges to the Future Initiative (BFI), a computer-aided instruction (CAI) intervention was launched in Andhra Pradesh to bring children back to school. The BFI used multimedia software to teach basic literacy and numeracy skills through interactive stories and activities, in the local language Telugu. The methodology employed in the study was a quasi experimental design on a sample of around 140 children (age range 7-19 years). The research study included BFI sites which offered two hours of CAI a day and comparison sites which provided five hours of teacher-based instruction (TBI) a day. According to several socio-economic indicators on the survey, the sample came from poor families with low literacy levels. Findings from the survey indicated that these out-of-school children had a positive attitude toward education and a favorable perception of educated people. A majority of the sample dropped out of school to assist with domestic tasks or family run businesses and did not earn wages. The impact analysis indicated that learning took place in both contexts and learners achieved similar learning gains between pretest and posttest. However, learners in the BFI intervention were learning at a faster pace per hour than learners in the comparison sites. Learners in the CAI intervention achieved similar gains as learners in the TBI intervention in one-third of the instruction time. As such, there is a strong case to be made for the BFI program being more efficient in raising levels of literacy and numeracy scores. Within the BFI intervention group, there was evidence to suggest that the number of days attended resulted in an increase in posttest scores, particularly in reading. Furthermore, older students in the BFI intervention had consistently shown higher gains in learning across reading, writing, math and information and communication technology (ICT) literacy domains. Finally, girls in the BFI sample outperformed the boys and the biggest difference in test scores was seen in Math. The impact of the BFI intervention could also be documented by the fact that approximately 45% of the BFI sample returned to school in the next academic year. In sum, this research was one of the first to explore the context of out-of-school children in poor communities and the use of CAI in Telugu (local language) to bring these learners back to school. The results support the use of ICT with marginalized sections of society in developing countries in order to improve literacy skills. The findings of this study have the potential to inform policy makers on educational and gender equity issues.
KerkoCite.ItemAlsoKnownAs: 2339240:JE6NXAA5 2405685:8XTQWYRM
Keywords: Bridges to the Future Initiative; Computer-aided instruction; Education; India; Information and communication technologies; Information and communication technology (ICT); Literacy; Out-of-school children; School dropouts

Culture and Classroom Reform: The case of the District Primary Education Project, India - Clarke, Prema (Comparative Education, 2003)
Reform in teaching and learning forms one of the basic dimensions of educational reform. This study explores the impact of the reform process on teacher thinking and classroom practice in the multi-donor supported District Primary Education Project in Karnataka, India. Using both qualitative and quantitative methodologies, a variety of aspects dealing with teaching and learning are examined in order to understand the extent to which changes are taking place in the classroom. The study analyses the impact of four cultural constructs, which frame teaching and learning in India: holism as a shared worldview that encourages openness to regulation; the hierarchical structure as a regulative social framework; knowledge as discovered and attested collectively; and the ‘sense of duty’ that deﬁnes the role of the teacher (and student). The conclusion of the study is that while there are observable changes in the classroom in the use of instructional aids and activities during instruction, the essential characteristics of traditional practice, namely rote and repetition has not changed. Both teachers’ openness and resistance to reform are portrayed as embedded in the cultural construction of teaching and learning.
shortDOI: 10/dj6jdc KerkoCite.ItemAlsoKnownAs: 10.1080/03050060302562 10/dj6jdc 2405685:J2IPL98G

Blogging as critical praxis: becoming a critical teacher educator in the age of participatory culture - Pascarella, John (McGill University, 2009)
This self-study of becoming a critical teacher educator extends the research on blogs as a vehicle of critical self-reflection in teaching and teacher education. While the primary focus of this thesis is a self-study of the process of becoming a teacher educator, the author presents findings based on discursive data collected from blogs produced by teacher candidates in two case studies, which inform this process of becoming. The case studies are represented as two “strands”: one carried out in Montréal, Quebec, Canada, at McGill University, and the other carried out near Durban, KwaZulu-Natal, South Africa, at the University of KwaZulu-Natal. Like prior studies involving the use of blogs in teacher preparation, this study examines pre-service teachers’ critical engagement with topics and issues endemic to their current field experiences and future careers in K-12 classrooms. The instructional techniques deployed in the case studies adhered to principles of modeling technology integration in order to transform teaching and learning activities by facilitating a learning environment for pre-service teacher candidates informed by the tenets of critical pedagogy. In this vein, this study examines the implementation of a particular instructional strategy, problem-posing pedagogy, as a practice that integrates the use of blogs to aid the achievement of pre-service teacher candidates’ “critical self-engagement” as well as contribute to the author’s development as a critical teacher educator.
ISBN: 978-0-494-61838-7 Publication Title: ProQuest Dissertations and Theses NR61838 Loc in Archive 305106950 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/305106950?accountid=9851 KerkoCite.ItemAlsoKnownAs: 2405685:3MNATQZE 2534378:IZK6PKSA 2534378:L3NWKKA3
Keywords: 0530:Teacher education; 0710:Educational technology; Blogging; Critical praxis; Culture; Education; Educational technology; Participatory culture; Teacher education; Teacher educator; __:import:01; __:match:final; __:matched; __:study_id:2097704; __finaldtb

Factors Affecting Technology Uses in Schools: An Ecological Perspective - Zhao, Yong; Frank, Kenneth A. (American Educational Research Journal, 2003)
Why is technology not used more in schools? Many researchers have tried to solve this persistent puzzle. The authors of this article report on their study of technology uses in 19 schools. They suggest an ecological metaphor, using the example of the introduction of the zebra mussel into the Great Lakes, to integrate and organize sets of factors that affect implementation of computer uses. Their findings suggest that an ecological perspective can provide a powerful analytical framework for understanding technology uses in schools. That perspective points out new directions for research and has significant policy and practical implications for implementing innovations in schools.
Publisher: American Educational Research Association zotzenLib.CopiedFrom: 2339240:LJV7RSEV KerkoCite.ItemAlsoKnownAs: 10.3102/00028312040004807 2339240:LJV7RSEV 2405685:KSZIKTG8
Keywords: computers in schools; diffusion of innovation; educational technology; school ecology; teacher development

Small-group problem-based learning as a complex adaptive system - Mennin, Stewart (Teaching and Teacher Education, 2007)
Small-group problem-based learning (PBL) is widely embraced as a method of study in health professions schools and at many different levels of education. Complexity science provides a different lens with which to view and understand the application of this method. It presents new concepts and vocabulary that may be unfamiliar to practitioners of small-group PBL and other educational methods. This article looks at small-group PBL from the perspective of complex adaptive systems (CAS). It begins with a brief review of the current understanding and practice of PBL. Next some of the characteristics of CAS are reviewed using examples from small-group PBL to illustrate how these characteristics are expressed in that context. The principles and the educational theory in which small-group PBL are embedded are related to CAS. Implications for health professions education are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2006.12.016 2339240:6J33JNEG 2339240:KJUSTUD8 2405685:DNHIV4ZM 2405685:X6ZBQLYW

Integrating technology into K-12 teaching and learning: current knowledge gaps and recommendations for future research - Hew, Khe Foon; Brush, Thomas (Educational Technology Research and Development, 2007)
Although research studies in education show that use of technology can help student learning, its use is generally affected by certain barriers. In this paper, we first identify the general barriers typically faced by K-12 schools, both in the United States as well as other countries, when integrating technology into the curriculum for instructional purposes, namely: (a) resources, (b) institution, (c) subject culture, (d) attitudes and beliefs, (e) knowledge and skills, and (f) assessment. We then describe the strategies to overcome such barriers: (a) having a shared vision and technology integration plan, (b) overcoming the scarcity of resources, (c) changing attitudes and beliefs, (d) conducting professional development, and (e) reconsidering assessments. Finally, we identify several current knowledge gaps pertaining to the barriers and strategies of technology integration, and offer pertinent recommendations for future research.
zotzenLib.CopiedFrom: 2339240:742UC4RT KerkoCite.ItemAlsoKnownAs: 10.1007/s11423-006-9022-5 2339240:742UC4RT 2405685:FCFEJK4Z

Qualitative Research: A Guide to Design and Implementation - Merriam, Sharan B. (John Wiley & Sons, 2009)
Praise for the Third Edition of Qualitative Research: "Sharan B. Merriam synthesizes twenty years of developments in qualitative research with clarity and acumen." ?Michael Quinn Patton, author, Qualitative Research and Evaluation Methods "Here is a qualitative research methods book that reinforces the connection between professional experience and qualitative inquiry." ?Robert Stake, author, The Art of Case Study Research and Multiple Case Study Analysis "In this new edition, Sharan Merriam once again presents the world of qualitative research in language engaging and accessible?for new and experienced readers alike. If you can have only one book about qualitative research, this is it!" ?Patricia M. Reeves, associate professor, School of Social Work, University of Georgia "Mystified by qualitative research? You couldn't ask for a better guide than Sharan Merriam, who introduces you to the fundamental concepts of this research method, explains its complex forms, and then shows you exactly how to do a high-quality qualitative study." ?M. Carolyn Clark, coeditor, The International Journal of Qualitative Studies in Education
KerkoCite.ItemAlsoKnownAs: 2339240:N3J2Y93P 2405685:7G2UTPZC
Keywords: Education / General

Emerging Technologies: An Overview of Practices in Distance Education - Hussain, Irshad (Journal on School Educational Technology, 2007)
In contemporary society, information technologies and communication technologies (ICTs) are playing crucial role in dissemination of knowledge and information the world over. Universities/ higher education institutions, particularly distance education universities in developed countries are making best use of these technologies for effective and interactive teaching learning process. Developing countries are also trying to adopt the model of developed countries according to their resources and circumstances. Distance education universities in developed countries like United States of America and United Kingdom are using advanced (emerging) technologies such as computers, Internet (World Wide Web) satellite communication, teleconferencing (videoconferencing and audio conferencing) and virtual reality in education and training. In developing countries like India, Pakistan and Thailand, distance education universities are using Radio, Television and Internet for teaching learning purpose and students support services. They are using computers mostly for office work. They are trying to adopt advanced technologies like developed countries but they have some limitations of resources (human & material resources). In future it is hoped that developing countries will also be using emerging technologies for teaching learning purpose.
Publisher: i-manager Publications KerkoCite.ItemAlsoKnownAs: 10.26634/jsch.3.2.751 2339240:C2AIV4L4 2405685:C5QWP7I4
Keywords: Case Studies; Computer Mediated Communication; Distance Education; Educational Development; Educational Practices; Educational Technology; Educational Television; Foreign Countries; Influence of Technology; Information Networks; Online Systems; Open Universities; Technological Advancement; Technology Integration; Technology Uses in Education; Telecommunications; Virtual Universities

Teacher Motivation in Sub-Saharan Africa and South Asia - Bennell, Paul; Akyeampong, Kwame (DFID, 2007)
This is one of a series of Education Papers issued by the Central Research Department of the Department For International Development. Each paper represents a study or piece of commissioned research on some aspect of education and training in developing countries. Most of the studies were undertaken in order to provide informed judgements from which policy decisions could be drawn, but in each case it has become apparent that the material produced would be of interest to a wider audience, particularly those whose work focuses on developing countries.This report synthesises the main findings and recommendations of an international research project on teacher motivation and incentives in sub-Sahara Africa and South Asia. The study has addressed the following four main questions: • To what extent is there a problem of poor motivation among teachers in sub-Saharan Africa and South Asia? Does this amount to a ‘crisis’, as has been suggested by some observers? • If so, what are the main reasons for poor teacher motivation? • How do poor motivation and incentives affect teacher performance and the overall effectiveness of national education systems? • What should be done to ensure that teachers are adequately motivated?
KerkoCite.ItemAlsoKnownAs: 2129771:5XS5KY3U 2339240:4YDHY6PL 2405685:25GLFYDL 2405685:WPFEWHNL 4556019:J65GX7JX
Keywords: C:sub-Saharan Africa and South Asia; ⛔ No DOI found

Short screening scales to monitor population prevalances and trends in non-specific psychological distress - Kessler, Ronald; Andrews, Gavin; Colpe, Lisa; Hiripi, E; Mroczek, Daniel; Normand, Sharon-Lise; Walters, Ellen; Zaslavsky, Alan (Psychological Medicine, 2002)
A 10-question screening scale of psychological distress and a six-question short-form scale embedded within the 10-question scale were developed for the redesigned US National Health Interview Survey (NHIS). Initial pilot questions were administered in a US national mail survey (N = 1401). A reduced set of questions was subsequently administered in a US national telephone survey (N = 1574). The 10-question and six-question scales, which we refer to as the K10 and K6, were constructed from the reduced set of questions based on Item Response Theory models. The scales were subsequently validated in a two-stage clinical reappraisal survey (N = 1000 telephone screening interviews in the first stage followed by N = 153 face-to-face clinical interviews in the second stage that oversampled first-stage respondents who screened positive for emotional problems) in a local convenience sample. The second-stage sample was administered the screening scales along with the Structured Clinical Interview for DSM-IV (SCID). The K6 was subsequently included in the 1997 (N = 36116) and 1998 (N = 32440) US National Health Interview Survey, while the K10 was included in the 1997 (N = 10641) Australian National Survey of Mental Health and Well-Being. Both the K10 and K6 have good precision in the 90th-99th percentile range of the population distribution (standard errors of standardized scores in the range 0.20-0.25) as well as consistent psychometric properties across major sociodemographic subsamples. The scales strongly discriminate between community cases and non-cases of DSM-IV/SCID disorders, with areas under the Receiver Operating Characteristic (ROC) curve of 0.87-0.88 for disorders having Global Assessment of Functioning (GAF) scores of 0-70 and 0.95-0.96 for disorders having GAF scores of 0-50. The brevity, strong psychometric properties, and ability to discriminate DSM-IV cases from non-cases make the K10 and K6 attractive for use in general-purpose health surveys. The scales are already being used in annual government health surveys in the US and Canada as well as in the WHO World Mental Health Surveys. Routine inclusion of either the K10 or K6 in clinical studies would create an important, and heretofore missing, crosswalk between community and clinical epidemiology.
KerkoCite.ItemAlsoKnownAs: 10.1017/S0033291702006074 2339240:INYZ8Z7T 2405685:5CNFKZP4

Paradigm Peace and the Implications for Quality - Bryman, Alan (International Journal of Social Research Methodology, 2006)
In this article it is shown that the paradigm wars that raged concerning the incompatibility of quantitative and qualitative research have largely subsided. In the process, discussions of epistemological and ontological issues have become less prominent. The peace that has broken out has proved to be more favourable to research combining quantitative and qualitative research than was the case during the paradigm wars. Drawing on interviews with social researchers who employ a mixed‐methods approach and on the literature, it is shown that a spirit of pragmatism with regard to combining quantitative and qualitative research prevails which encourages researchers to consider using mixed‐methods research when the research question is suited to it. However, the issue of which quality criteria should be employed in investigations combining quantitative and qualitative research has not been given a great deal of consideration. The author argues for a contingency approach, in which issues to do with quality are decided in relation to the nature of the study.
shortDOI: 10/b8wtt2 KerkoCite.ItemAlsoKnownAs: 10.1080/13645570600595280 10/b8wtt2 2339240:T3KNAFUP 2405685:RKS7ELJH

Promoting academic literacy with technology: successful laptop programs in K-12 schools - Warschauer, Mark; Grant, David; Real, Gabriel Del; Rousseau, Michele (System, 2004)
One of the main challenges that US schools face in educating English language learners is developing their academic literacy. This paper presents case studies of two K-12 schools that successfully employ high-technology environments, including laptop computers for each student, toward the development of English language learners’ academic language proficiency and academic literacy. In the first school, Latino fourth-grade students use laptops and other new technologies for a wide variety of pre- and post-reading tasks as part of their effort to transition from learning to read to reading to learn. In the second school, diverse immigrant and refugee students at the middle school level combine technology use with Expeditionary Learning to carry out community projects leading to the development of sophisticated products. In both schools, technology is used to engage students in cognitively demanding activity, motivate independent reading, and provide scaffolding for language development, while the researchers also made use of technology to document learning processes and outcomes. Taken together, the schools offer valuable lessons for utilization of technology to promote academic literacy among culturally and linguistically diverse students.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.system.2004.09.010 10/ffr68w 2339240:CR5JUUTC 2405685:9TQ7P4IC
Keywords: Laptops; Literacy; Technology

Exploring the backgrounds and shaping of beginning student teachers in Ghana: toward greater contextualisation of teacher education - Akyeampong, Kwame; Stephens, David (International Journal of Educational Development, 2002)
Teacher education programmes are often quite similar in their framework and content but often lack sufficient reflection on the personal background and the socio-political forces that shape teachers’ roles and identity within the systems in which they operate. This paper explores this issue by using Ghana as a case study and discusses implications for its teacher education programmes and policies. Key characteristics of beginning student teachers found were: weak qualifying grades in two fundamental school subjects, mathematics and English, a waiting period of 2–5 years prior to entering teachers’ college, and apparently sharp differentials in trainees’ socio-economic background as compared to typical Ghanaian communities. They come to training with rich and varied images of teachers, teaching and the profession, but, in addition, many beginning trainees also express little desire to teach at primary school level, mainly for reasons of status and insufficient fringe benefits. These factors, we argue, should be taken into more account in the design of college programmes and the development of teacher education policies. The paper concludes with a call to teacher education systems, especially in Africa, to look more closely at, and learn from, who comes for training, what they bring with them, and how they perceive themselves in relation to teaching, training and future aspirations.
shortDOI: 10/fh448b KerkoCite.ItemAlsoKnownAs: 10.1016/S0738-0593(01)00064-5 10/fh448b 2405685:SHM89KC8
Keywords: Beginning student teachers; Ghana; Teacher education; Teacher identity; Teacher images

Investigating educational change: The Aga Khan University Institute for educational development teacher education for school improvement model - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2007)
This article continues the analyses of the impact of an innovative teacher education programme aimed at school improvement in a developing country context (A. Khamis, P. Sammons, 2004. The development of a cadre of teacher educators: some lessons from Pakistan. International Journal of Educational Development, 24(3), 255–268). Building on recent publications that have analysed outcomes of the teacher education programme and how the cadre of teacher educators has worked to initiate improvement in schools in Pakistan. The article considers the ‘teacher education for school improvement model’ based on findings from the case studies of nine co-operating school. Lessons are presented to further inform the development of teacher education programmes and the measurement of effectiveness of such programmes in developing country contexts. The article further considers relevant international research on educational change and reform to draw further lessons. These lessons include the need to pay greater attention to the cultural contexts and milieu in Pakistan, and the need to create models of school improvement and teacher education that originate within developing country contexts rather than the adaptation of European/North American models that are based on sources of data in those contexts. The article concludes by arguing for the need to develop better theoretical understandings from the current innovations underway and placing the onus on intervening agencies to better inform educational change strategies promoted in developing country contexts.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2006.12.006 2339240:9NIU3EAU 2405685:AVG9NPXF
Keywords: Developing countries; Educational change; Innovation; Pakistan; School improvement; Teacher education

Using learning design as a framework for supporting the design and reuse of OER - Conole, Gráinne; Weller, Martin (Journal of Interactive Media in Education, 2008)
The paper will argue that adopting a learning design methodology may provide a vehicle for enabling better design and reuse of Open Educational Resources (OERs). It will describe a learning design methodology, which is being developed and implemented at the Open University in the UK. The aim is to develop a 'pick and mix' learning design toolbox of different resources and tools to help designers/teachers make informed decisions about creating new or adapting existing learning activities. The methodology is applicable for designers/teachers designing in a traditional context – such as creation of materials as part of a formal curriculum, but also has value for those wanting to create OERs or adapt and repurpose existing OERs. With the increasing range of OERs now available through initiatives as part of the Open Courseware movement, we believe that methodologies, such as the one we describe in this paper, which can help guide reuse and adaptation will become increasingly important and arguably are an important aspect of ensuring longer term sustainability and uptake of OERs. Our approach adopts an empirically based approach to understanding and representing the design process. This includes a range of evaluation studies (capturing of case studies, interviews with designers/teachers, in-depth course evaluation and focus groups/workshops), which are helping to develop our understanding of how designers/teachers go about creating new learning activities. Alongside this we are collating an extensive set of tools and resources to support the design process, as well as developing a new Learning Design tool that helps teachers articulate and represent their design ideas. The paper will describe how we have adapted a mind mapping and argumentation tool, Compendium, for this purpose and how it is being used to help designers and teachers create and share learning activities. It will consider how initial evaluation of the use of the tool for learning design has been positive; users report that the tool is easy to use and helps them organise and articulate their learning designs. Importantly the tool also enables them to share and discuss their thinking about the design process. However it is also clear that visualising the design process is only one aspect of design, which is complex and multi-faceted. Editors: Alexandra Okada (Open University, UK). Reviewers: Teresa Conolly (Open University, UK), Rose Luckin (Institute of Education, UK), and Alexandra Okada (Open University, UK)
shortDOI: 10/ghgn54 KerkoCite.ItemAlsoKnownAs: 10/ghgn54 2405685:PTSWVK6M
Keywords: IMS learning design; Learning Design; e-learning; mind mapping

Universal Design for Learning: Is It for Everyone? - Rose, D; Meyer, A (2006)
Universal Design for Learning (UDL) stands at the forefront of contemporary efforts to create universal access to educational curricula for all students, including those with disabilities. The "universal" in UDL does not mean there is a single optimal solution for everyone. Instead, it underscores the need for flexible approaches to teaching and learning that meet the needs of different kinds of learners. In this first UDL Reader, Anne Meyer and David H. Rose, cofounders of CAST, the educational nonprofit that developed the UDL framework, bring together a collection of articles on the practical, classroom dimensions of the UDL revolution in education. The authors offer insights on learner differences, the capacities of new media in the classroom, and effective teaching and assessment practices. The volume also includes lessons from teacher professional development workshops, classroom-based research, and UDL practitioners themselves. A highly readable volume aimed particularly at school teachers and administrators, this book is also an uncommonly accessible introduction to UDL for all readers committed to creating improved and universal access to educational materials for all students. Following a preface (Anne Meyer and David H. Rose), this book contains the following chapters: (1) Applying Universal Design for Learning in the Classroom (Peggy Coyne, Patricia Ganley, Tracey Hall, Grace Meo, Elizabeth Murray, and David Gordon); (2) A UDL Case Story and Model Lesson: Reading Challenges in Geography and Social Studies (The Staff at CAST); (3) Frequent Questions about Universal Design for Learning (Grace Meo); (4) A Level Playing Field: UDL in the Classroom (Lani Harac); (5) Teacher Perspectives: UDL in the Elementary Classroom (Kirsten Lee Howard); (6) Teacher Perspectives: Strategy Instruction Goes Digital (Nicole Strangman); (7) Implications of Universal Design for Learning for Classroom Assessment (David H. Rose and Robert P. Dolan); (8) The Promise of New Learning Environments for Students with Disabilities (Bart Pisha and Skip Stahl); (9) Transforming the Textbook to Improve Learning (Skip Stahl); (10) Engaging the Text: Brain Research and the Universal Design of Reading Strategy Supports (David H. Rose and Bridget Dalton); and (11) Teaching Internet Literacy Strategies: The Hero Inquiry Project (Maya B. Eagleton, Kathleen Guinee, and Karen Langlais). An index is also included.
KerkoCite.ItemAlsoKnownAs: 2339240:RTHAM8C5 2405685:2IJJICCL